2012
DOI: 10.1016/j.pscychresns.2011.08.011
|View full text |Cite
|
Sign up to set email alerts
|

A window into the brain: An in vivo study of the retina in schizophrenia using optical coherence tomography

Abstract: Retinal nerve fibre layer (RNFL) thickness and macular volume (MV) can be measured in vivo using optical coherence tomography (OCT) providing a “window into the brain”. RNFL and MV are promising biomarkers in neurological diseases. This study explores the potential of RNFL and MV to detect axonal abnormalities in vivo in schizophrenia and their correlations with clinical features. OCT was performed in 49 patients (38 schizophrenia, 11 schizoaffective disorder) and 40 healthy controls matched for age and gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 37 publications
6
90
1
3
Order By: Relevance
“…In the first study reported in the literature, our group found a decreased RNFL thickness as measured with OCT in patients with schizophrenia (Ascaso et al, 2010). Similar results have been later reported by Lee et al (2013), who additionally found a relationship between abnormal OCT parameters and illness duration, but not by Chu et al (2012), who did not find significant differences in retinal parameters between patients in the early stages of illness and controls.…”
Section: Introductionsupporting
confidence: 89%
“…In the first study reported in the literature, our group found a decreased RNFL thickness as measured with OCT in patients with schizophrenia (Ascaso et al, 2010). Similar results have been later reported by Lee et al (2013), who additionally found a relationship between abnormal OCT parameters and illness duration, but not by Chu et al (2012), who did not find significant differences in retinal parameters between patients in the early stages of illness and controls.…”
Section: Introductionsupporting
confidence: 89%
“…Indeed, the volume of the macula was reduced, the thickness of both macula and RNFL was decreased and the thinning/reduction were correlated with the duration of the disease (Lee et al, 2013). Using the same technique, another team failed to replicate the thinning of the macular and the RNFL but found that the macular volume was negatively correlated with the severity of positive symptoms (Chu et al, 2012).…”
Section: The Retinal Levelmentioning
confidence: 99%
“…Bu araştırmada kullanılan OKT aygıtının eski teknolojiye sahip olması, araştırmacılar tarafından da sınırlılık olarak belirtilmiştir. 7 Çalışmamızda kullanılan spektral OKT aygıtı, RSL ve GHIP tabakasını ölçebilmek-tedir. Bu aygıt son dönemde şizofrenide retina tabakalarını araştırmak için kullanılan OKT aygıtlarına benzer teknolojidedir, duyarlı ve iyi çözünürlükte sonuç verebilmektedir.…”
Section: Discussionunclassified
“…3,4 Optik sinirin merkezi sinir sistemi (MSS) ile ortak embriyolojik yapıdan (nöro-ektoderm) köken alması nedeni ile OKT ile ölçülen retina tabaka değişikliklerinin, beyinde oluşan nörodejenerasyonu doğrudan yansıtabi-leceği ileri sürülmüştür. [5][6][7] OKT, Parkinson, bunama, multipl skleroz (MS) gibi MSS hastalıklarının tanı ve izlemelerinde kullanılmaktadır. [8][9][10][11] Şizofreni hastalarında OKT, MSS'nin diğer hastalıklarına göre daha az sayıda araştırmada kullanılmıştır.…”
Section: Introductionunclassified